Tinjauan Etika Bisnis Islam Terhadap Strategi Pemasaran Dengan Metode Decoy Effect - Muhammad Abduh; Elif Pardiansyah (Syi`ar Iqtishadi : Journal of Islamic Economics, Finance and Banking, 2022)
The marketing strategy used by sellers to get consumers to switch from one option to a more expensive or profitable option is called the decoy effect. This study uses a qualitative research method with a literature study approach. The result of this study is the decoy effect is a phenomenon where consumers change their preferences from the previous two choices to the third choice when presented with a third choice that acts as an asymmetrical dominating bait. Decoy is an action that can lead to manipulation activities and has a strong orientation towards achieving maximum profit and can be categorized as false economic activity. For consumers, the wrong perception about shopping choices can cost them more money (mubadzir). According to the first view, if the comparison of price and quantity or quality obtained by customers is still in a reasonable stage, then this strategy is highly recommended to boost sales. Meanwhile, according to the second view, the decoy effect does not reflect 'iwad al mits (equivalent compensation) and nafs al-'adl in Islamic business transactions.